Relation between children's math grades and attitudes and parents' attitudes toward mathematics - Arambašić, Lidija; Vlahović-Štetić, Vesna (2003)
Parents' attitudes play an important role in the mathematics achievement and children's attitudes (Jacobs, 1991). The aim of the study was to find out effects of mothers' and fathers' math attitudes and children's gender and age on children's math attitudes and grades. Participants were 250 elementary school students (11 to 14 years) and their parents. The questionnaire about beliefs and attitudes about mathematics was administered to students during regular class and to parents during parental meeting. Math grades at the end of first semester were also collected. Results on children's attitudes were analyzed by two separate analyses of variance (children' gender X age X parental positive/negative attitude), one for fathers and the other for mothers. Results on children's grade were analyzed in the same way. Obtained results confirmed some hypotheses about the effects of mothers' and fathers' math attitudes and children's gender and age on children's math attitudes and grades.
Projekt MZOS
ENG